The Estimation of Petrol's Demand Function in Iran During 1968-2002 - Abbas Ali Aboonoori; Hiva Shiveh (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2006)
In this paper our intention is to introduce some effective variables on petrol consuming, and demand function for petrol in Iran. Also we want to show why different consumer policies can't change demand for petrol on optimal manner. This is done by using statistical and econometrics analyses, we estimate the demand for petrol and then show that which one of exogenous variable like price of petrol, growth of population, number of vehicles and growth national income have had  more effective on stimulating of demand for petrol in Iran during 1968 to 2002. That is there is very small relation between price and demand for petrol; also there is very good relation between demand for petrol and three parameters in our results.